1988
DOI: 10.1128/aac.32.9.1430
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of beta-lactamase plasmids from Neisseria gonorrhoeae to Neisseria meningitidis and commensal Neisseria species by the 25.2-megadalton conjugative plasmid

Abstract: Two highly tetracycline-resistant, ,-lactamase-producing Neisseria gonorrhoeae strains were used as donors for conjugation with Neisseria meningitidis and commensal Neisseria species. We found that both strains were able to transfer the 4.4-and 3.2-megadalton ,-lactamase plasmids to the recipients tested, with frequencies between 10-' and 10-9.The gonococcal P-lactamase plasmids were first described in 1977 (19). Since that time, they have become endemic in North America, and they are common in other parts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Thus, plasmid pMR9418 is similar to other conjugative Haemophilus R plasmids in this characteristic and differs from the cryptic H. ducreyi conjugative plasmid described previously (7). This, along with the fact the 25.2-MDa plasmid retained its ability to mobilize 13-lactamase plasmids (25,26), suggests that the ancestor of pMR9418 may not be the cryptic H. ducreyi plasmid described previously, but more work is needed to confirm this hypothesis.…”
mentioning
confidence: 76%
“…Thus, plasmid pMR9418 is similar to other conjugative Haemophilus R plasmids in this characteristic and differs from the cryptic H. ducreyi conjugative plasmid described previously (7). This, along with the fact the 25.2-MDa plasmid retained its ability to mobilize 13-lactamase plasmids (25,26), suggests that the ancestor of pMR9418 may not be the cryptic H. ducreyi plasmid described previously, but more work is needed to confirm this hypothesis.…”
mentioning
confidence: 76%
“…In all cases, the ,B-lactamase plasmid was associated with the 25.2-MDa plasmids in the transconjugants. We found that the N. cinerea transconjugants were exceptions to this generalization because when they were used as recipients, the ,-lactamase plasmids were found without the 25.2-MDa plasmids (36). Recently, P-lactamaseproducing N. meningitidis strains have been described (3,9).…”
Section: (5)mentioning
confidence: 92%
“…When introduced into the commensal Neisseria spp., the P-lactamase plasmids were very unstable and were quickly lost from most of the recipient strains. In a later study, Ikeda et al (21) Recently, using strains containing both the P-lactamase plasmid and the 25.2-MDa tetracycline resistance conjugative plasmid, we mobilized the 4.4-and 3.2-MDa P-lactamase plasmids into a variety of Neisseria spp., including N. meningitidis (36). A number of the transconjugants maintained the P-lactamase plasmids in the absence of selective antibiotic pressure.…”
Section: (5)mentioning
confidence: 99%
“…A plasmid containing the resistance gene to tetracycline, tetM, identified in N. gonorrhoeae, has shown the capability to be transferred in vitro to N. meningitidis (Roberts & Knapp, 1988). Since both species can occasionally co-exist in the genitourinary tract or in the nasopharynx, it has been speculated that transfer of resistance plasmids may also occur in vivo (Dillon et al, 1983).…”
Section: Chemotherapy and Antibiotic Resistancementioning
confidence: 99%